2011
DOI: 10.1017/s0029665111000036
|View full text |Cite
|
Sign up to set email alerts
|

Improving the dietary intake of frail older people

Abstract: As a population subgroup, older people are more vulnerable to malnutrition especially those who are institutionalised. Recognition of deteriorating or poor nutritional status is key in reversing the effects of undernutrition and reinforces the value of regular weight checks and/or the use of screening tools. Commercially produced supplements are often the first option used to address undernutrition in both acute and community settings. They can be expensive and, although regularly prescribed, have undergone on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
1
19
0
2
Order By: Relevance
“…All participants were provided with similar instructions, and were given enough time and enough of each drink to make all ratings. All participants were required to report no known taste impairments prior to participation, but we took no account of illnesses, medication use, dentition, oral health or other similar factors that may impact on taste without a participant being aware ( Duffy et al, 1999 ; Griep et al, 1997 ; Leslie, 2011 ; Koskinen et al, 2003 ; Kremer, Bult, et al, 2007b , Kremer, Mojet, et al, 2007 ). Furthermore, illness, medication use, etc, are likely to increase with age, thus our effects of age may be due to increased illness, etc, as opposed to advanced years ( Kremer, Mojet, et al, 2007c ), but the practical implications of this distinction are negligible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants were provided with similar instructions, and were given enough time and enough of each drink to make all ratings. All participants were required to report no known taste impairments prior to participation, but we took no account of illnesses, medication use, dentition, oral health or other similar factors that may impact on taste without a participant being aware ( Duffy et al, 1999 ; Griep et al, 1997 ; Leslie, 2011 ; Koskinen et al, 2003 ; Kremer, Bult, et al, 2007b , Kremer, Mojet, et al, 2007 ). Furthermore, illness, medication use, etc, are likely to increase with age, thus our effects of age may be due to increased illness, etc, as opposed to advanced years ( Kremer, Mojet, et al, 2007c ), but the practical implications of this distinction are negligible.…”
Section: Discussionmentioning
confidence: 99%
“…This under-nutrition is a result, at least in part, of low levels of consumption ( Cowan et al, 2004 ; Leslie, 2011 ). Liking is a strong determinant of consumption in older adults ( Appleton, McGill, Neville, & Woodside, 2010 ; Best & Appleton, 2013 ; Leslie, 2011 ), but various reports demonstrate lower ratings for liking or the pleasantness of food items in older compared with younger individuals ( de Graaf, Polet, & van Staveren, 1994 ; de Graaf, van Staveren, & Burema, 1996 ). These lower likings have been strongly linked to decreases in chemosensory abilities ( de Graaf et al, 1994 , 1996 ; Kalviainen, Roininen, & Tuorila, 2003 ).…”
mentioning
confidence: 99%
“…Several factors should be considered when preparing the model approach. In order to fulfil consumer needs, expectations and preferences, the product and its packaging should also somehow address functional and cognitive limitations of older people (Leslie, ). In this way, older consumers will begin to be appreciated as consumers capable of purchasing more goods and services.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found quality indicators, such as the presence of adapted guidelines and policies, and the systematic education of staff, to be meaningful for the improvement of nutritional care practices ( 8 - 10 ). These quality indicators, together with nutritional competence and attitude, are described as vital for achieving interventions addressing malnutrition ( 11 - 13 ). Studies of links between food service practice and residents’ risk of malnutrition have further reported that overall meal satisfaction and menu cycle length, among other quality indicators, are associated with nutritional status ( 14 ).…”
Section: Introductionmentioning
confidence: 99%